Transition from Children’s to Adult Services for Patients with ADHD: A Model of Care - Moosa, Faizal; Sandhu, Tanveer (Adolescent Psychiatry, 2015)
Background: ADHD, a common childhood psychiatric disorder, is known to persist into adulthood. Gaps and needs in the care of adolescents having ADHD when moving on from Children’s Mental Health Services (CAMHS) to Adult Mental Health Services (AMHS) exist and result in disruptions in care and lack of care. This report describes the outcome of a quality improvement project in Birmingham in the United Kingdom that focused on the patient journey and continuity of care. Method: A CAMHS/AMHS transition (strategic) working group and a CAMHS ADHD transition (operational) team were set up. A validated dataset of those requiring transition was created and patient needs were reviewed. Planning and preparation for transition took place. The handover from CAMHS to AMHS was done at a joint clinic involving both services. Results: Over a 12-month period, the number of patients on the waiting list for transfer from CAMHS to AMHS went from 134 to 14 and the waiting time for transition between the two services went from 12 months to four months. The referral rate for those in need of transfer from CAMHS to AMHS was optimised. The rate of successful handover (and transition) went from 18% to 55% after the introduction of the joint clinics. Conclusion: A collaborative effort between CAMHS and AMHS, including the holding of joint clinics, ensured there was a comprehensive and effective transition care pathway in place for adolescents with ADHD.
Keywords: ADHD